2a3 - 128 = 2*(a3 - 64) = 2*(a -4)*(a2 + 4a + 16)
(a - b + 2)(a + b + 2)
The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3
(4a)2 or 16a2
there are 2
The expression 4a - 5 - a + 2 can be simplified by combining like terms. Combining the terms with 'a', we get 4a - a = 3a. Combining the constants, we get -5 + 2 = -3. Therefore, the simplified expression is 3a - 3.
2a3 - 128 = 2*(a3 - 64) = 2*(a -4)*(a2 + 4a + 16)
a-16 = a/4+2 Multiply all terms by 4: 4a-64 = a+8 4a-a = 8+64 3a = 72 a = 24
It is an expression that can be simplified to: 4a+2
It is 4a2.
(a - b + 2)(a + b + 2)
a = -2-4a/3-2 = 8-4a = 8(3-2) times both sides by (3-2)-4a = 24-16-4a = 8-a = 2 divide both sides by 4a = -2 times both sides by -1
The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3
4a + 7
−4a + 139 = 4a + 123 → −8a = −16 → a = 24a + 123 → 4(2) + 123 = 8 + 123 = 131°
8
(a + 4)(a^2 - 4a + 16)